Chronic exercise induced compartment syndrome - van Zoest, W.; Hoogeveen, A. (Medicine and Science in Tennis, 2006)
Chronic exercise-induced compartment syndrome (CECS) is a sports-related injury that is characterized by pain and loss of function during muscle activity. Pain is ischemic in character and is caused by a non-physiological rise in compartment pressure impeding sufficient circulation. CECS may develop in any muscle harbouring an enveloping fascia, such as the thigh, the arm, and even the foot. Lower extremity CECS may be present in all four compartments (anterior, lateral, superficial and deep posterior), but usually the anterior compartment is involved. Typically, such CECS occurs when individuals dramatically increase the amount of walking or running, for example tennis players who increase their training intensity and specifically increase the amount of running they do. CECS may also occur in the deep posterior compartment of the leg. In contrast to anterior CECS, a patient's history is much more indistinct in posterior CECS, as associations with medial shin splints as well as tibial stress fractures may be present. When conservative treatments, such as inlays or adjustment of training intensity, fails, surgical intervention by means of fasciotomy or fasciectomy is the main operative treatment.